Personal Factors Affecting Whistleblowing Among Public Sector Employee - Defiantoro, Dwi; Mayasari, Ima (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Whistleblowing is a difficult choice among the witnesses of wrongdoing. This study investigates what influences the decision to report such incidents within the Indonesian Public Administration, focusing on individual factors. Using quantitative research methods, data were collected from 406 Indonesian public sector workers via a convenience survey and snowball sampling. The results reveal that the likelihood of whistleblowing is significantly influenced by confidence in the reporting channel's management, social anxiety, individualism and collectivism, the propensity to blow the whistle, and the individual's locus of control. Moreover, the PBW acts as a moderator on the effect of individual's locus of control. To increase the tendency towards whistleblowing, the study suggests that authorities should bolster legal safeguards for informants, including anti-reprisal actions, legal protection and organizational backing for support networks.